Extracurricular Implementation of Students' Interpersonal Intelligence at MIN 2 Kediri - Nisa, Zahrotun; Dini, Sri Susanti Tjahja; Mustamir, Ahmad Khoirul (Indonesian Journal of Elementary Education (IJEE), 2025)
The focus of this research is how students at MIN 2 Kediri can enhance their interpersonal intelligence through extracurricular activities. A person's ability to understand, interact, and build social relationships is known as interpersonal intelligence, which is an important component of multiple intelligences. This research uses a descriptive qualitative approach that collects data through observation, in-depth interviews, and documentation. Students, the principal, and extracurricular activity supervisors are the subjects of this research. The research results show that extracurricular activities at MIN 2 Kediri, such as scouting, hadrah, dance arts, and sports, are conducted systematically and focus on the development of students' social character. Through group activities, students are encouraged to communicate actively, cooperate, appreciate differences, and demonstrate empathy and leadership qualities. The process of implementing these activities is also supported by the active role of the mentors who regularly guide and evaluate the students. The results of this study indicate that extracurricular activities significantly contribute to the development of students' interpersonal intelligence. In order for extracurricular programs to effectively develop students' social skills as a whole, teachers, parents, and the school environment must collaborate more effectively.Keywords: Extracurricular Activities, Interpersonal Intelligence